Genetically Encoded Calcium Indicators: A New Tool in Renal Hypertension Research - Zhong, Cheng; Schleifenbaum, Johanna (Frontiers in Medicine, 2019)
Hypertension is ranked third cause of disability-adjusted life-years. The percentage of population suffering from hypertension will still increase over the next years. Renovascular disease is one of the most common causes of secondary hypertension. Vascular changes seen in hypertension are partially based on dysfunctional calcium signaling. This signaling can be studied using calcium indicators (loading dyes and genetically encoded calcium indicators; GECIs). Most progress in development has been seen in GECIs, which are used in an increasing numbers of publications concerning calcium signaling in vasculature and kidney. The use of transgenic mouse models expressing GECIs will facilitate new possibilities to study dysfunctional calcium signaling in a cell type-specific manner, thus helping to identify more specific targets for treatment of (renal) hypertension.